Determinants of environmental degradation: reflections on the impact of identified economic variables on the environment - Ramayah, M; Rasiah, R; Somasundram, S; Turner, J.J. (National Mining University, 2019)
Purpose. The main objective of this study is to investigate the determinants of environmental degradation within the broader framework of the environmental Kuznets Curve analysis. To better understand the economic impact on the environment, the study focuses on the relationship between carbon emission and the variables income per capita, trade openness, foreign direct investment, energy use and urbanization. Methods. In the context of the dynamic carbon emission model a Generalized-Method-of-Moments (GMM) technique was used to analyse World Bank of 125 countries for the period 2000 to 2014. This era was chosen as the most appropriate given the completeness of the dataset. Findings. The findings indicate that economic growth and energy use are significant variables in explaining environmental degradation, supporting previous research in to the particularly negative impact of energy use on the environment. The research however, found that urbanisation had only marginal significance in explaining the impact on the environment. Originality. The findings contribute to existing research in the area of environmental degradation, providing insight into the debate surrounding urbanisation and CO2 emission which had previously received mixed results. The findings take research forward through the examination of explanatory variables and their respective impact on CO2 emission in countries which have observed an increase in the number of urban dwellers. Practical implications. Given the debate in academic and practitioner literature around climate change, pollution and a general concern over a lack of collective action to address environmental concerns, the findings have practical implications for government institutions and businesses to better understand the economic impact on the environment.

Мета. Визначення факторів, які викликають екологічну деградацію довкілля в широкому контексті екологічної кривої Кузнеця, на основі вивчення взаємозв’язку між вуглецевими викидами і такими змінними як дохід на душу населення, відкритість торгівлі, прямі іноземні інвестиції, використання енергії та урбанізація. Методика. Для побудови динамічної моделі вуглецевої емісії були використані дані Всесвітнього банку по 125 країнам у період з 2000 по 2014 роки, проаналізовані за допомогою узагальненого методу моментів. Даний проміжок часу був обраний як той, що найбільш повно представляє базу даних. Результати. Встановлено, що економічне зростання і використання енергії є найсуттєвішими факторами, які визначають екологічну деградацію, що підтверджується більш ранніми дослідженнями негативного впливу використання енергії на навколишнє середовище. Виявлено, що урбанізація впливає на стан навколишнього середовища тільки побічно. Рекомендовано в наступних дослідженнях розглянути інші заходи для уявлення урбанізації, а саме можливість вивчення даних по великих містах, а не по країнам. Такий підхід може дати додаткове уявлення про вплив урбанізації та можливих відмінностей між містами і регіонами. Наукова новизна. Отримано нові знання щодо оцінки впливу урбанізації та вуглецевих викидів на навколишнє природне середовище, які раніше мали неоднозначні результати. Прогрес у вивченні даних проблем було досягнуто за рахунок аналізу ключових змінних і їх впливу на емісію CO2 в країнах, де спостерігається зростання міського населення. Практична значимість. Результати дослідження мають істотне практичне значення для державних установ та бізнесових структур, оскільки допомагають краще зрозуміти сутність економічного впливу на навколишнє середовище і вносять вклад у вирішення проблеми екологічної деградації.

Цель. Определение факторов, вызывающих экологическую деградацию окружающей среды в широком контексте экологической кривой Кузнеца, на основе изучения взаимосвязи между углеродными выбросами и такими переменными как доход на душу населения, открытость торговли, прямые иностранные инвестиции, использование энергии и урбанизация. Методика. Для построения динамической модели углеродной эмиссии были использованы данные Всемирного банка по 125 странам в период с 2000 по 2014 годы, проанализированные при помощи обобщенного метода моментов. Данный промежуток времени был выбран как наиболее полно представляющий базу данных. Результаты. Установлено, что экономический рост и использование энергии являются самыми существенными факторами, определяющими экологическую деградацию, что подтверждается более ранними исследованиями негативного влияния использования энергии на окружающую среду. Выявлено, что урбанизация воздействует на состояние окружающей среды только косвенно. Рекомендовано в следующих исследованиях рассмотреть другие меры для представления урбанизации, а именно возможность изучения данных по крупным городам, а не по странам. Такой подход может дать дополнительное представление о влиянии урбанизации и возможных различий между городами и регионами. Научная новизна. Получены новые знания касательно оценки влияния урбанизации и углеродных выбросов на окружающую природную среду, которые ранее имели неоднозначные результаты. Прогресс в изучении данных проблем был достигнут за счет анализа ключевых переменных и их влияния на эмиссию CO2 в странах, где наблюдается рост городского населения. Практическая значимость. Результаты исследования имеют существенное практическое значение для государственных учреждений и бизнес структур, поскольку помогают лучше понять сущность экономического воздействия на окружающую среду и вносят вклад в решение проблемы экологической деградации.
Keywords: carbon emissions; GDP per capita; foreign direct investment; energy consumption; trade openness; urbanisation; developing countries